Descriptions of three new species of Bembidion Latreille (Coleoptera: Carabidae) occurring in Canada - Bousquet, Yves; Webster, Reginald (Zootaxa, 2006)
Three new species of Bembidion Latreille occurring in Canada are described: B. (Semicampa) nigrivestis Bousquet, sp. nov., type locality: Sainte-Catherine-de-Hatley (45°15’N, 72°03’W), Quebec; B. (Eupetedromus) iridipenne Bousquet and Webster, sp. nov., type locality: Lincoln (45° 49’N, 66°35’W), New Brunswick; and B. (Neobembidion) nitidicolle Bousquet, sp. nov., type locality: Rosefield (49°05’N, 107°32’W), Saskatchewan. A new subgenus, Neobembidion Bousquet, subgen. nov. (type species: Bembidion constricticolle Hayward, 1897), is proposed for the species of the constricticolle group as defined by Lindroth. Keys are included to distinguish the new species from their North American relatives.